Case report: First isolation of Yersinia pseudotuberculosis from the blood of a cat - Scarpellini, Raffaele; Giunti, Massimo; Bulgarelli, Cecilia; Mondo, Elisabetta; Esposito, Erika; Assirelli, Giammarco; Piva, Silvia (Frontiers in Veterinary Science, 2024)
A 14-year-old female domestic short-haired cat with a diagnosed diabetes mellitus and acromegaly was presented for lethargy and dysorexia. On clinical presentation, the patient showed hyperglycemia, hyperthermia, dull mentation, and dehydration. With the suspicion of an inflammatory or infectious complication of diabetes, she was hospitalized with constant rate infusion of insulin, and empirical ampicillin sulbactam was started. Blood culture revealed positivity for Yersinia pseudotuberculosis and the septic picture was confirmed by blood analysis, with leukocytosis, neutrophilia, and an increased serum amyloid A concentration. The isolated Y. pseudotuberculosis strain showed susceptibility to every antimicrobial tested. During the second day of hospitalization, the onset of hypoglycemia and hypotension was treated with norepinephrine and glucose in fluid therapy. The cat recovered well and was discharged with insulin and amoxicillin-clavulanate. This is the first case of septicemia associated with Y. pseudotuberculosis in a cat, suspected of developing the infection after contact with natural reservoirs such as rodents or birds. This route of transmission should be highlighted especially in relation to the zoonotic potential of the bacteria.